Prevalence of dental caries, periodontitis, and oral hygiene status among 12-year-old schoolchildren having normal occlusion and malocclusion in Mathura city: A comparative epidemiological study - Geetika Arora; Sumit Bhateja (Wolters Kluwer Medknow Publications, 2015)
Objective: The aim was to find the prevalence of dental caries, periodontitis, and oral hygiene index-simplified (OHI-S) among 12-year schoolchildren having normal occlusion and malocclusion in Mathura city. Materials and Methods: The present study was a cross-sectional study done among the 100 subjects who have been selected from 5 schools in four different geographical locations. The data regarding their socio-demographic characteristics, dental caries status, periodontitis status and oral hygiene status was collected using structured proforma. Means, standard deviations and test of significant were used as statistics to describe the data. Results: The results showed that there was no significant difference between dental caries status, periodontitis status among subjects having normal occlusion and malocclusion (P = 0.06, 0.093) but significant relationship was found OHI-S and children who were having malocclusion (and P = 0.022). Significant difference was also found between periodontitis and oral hygiene status (P = 0.00). Conclusion: It was observed from the present study that normal occlusion and malocclusion had no or weak significant effect on overall caries and periodontitis prevalence whereas oral hygiene status had a strong effect on overall periodontitis prevalence but not in relation to prevalence of dental caries in 12-year-old school children in Mathura city.